On Degree-Based Topological Indices of Thermodynamic Cuboctahedral Bi-Metallic Structure - Guozhen Ma; Muhammad Ibrahim; Ghazanfar Abbas; M. K. Siddiqui; Samuel Asefa Fufa (Journal of Mathematics)
Porous material such as metal-natural constructions and their particular partner metal-natural poly-hydra are made up of inorganic clusters with no saturation and exhibit great capability for utilization in the absorption of gas and ascending opening in optics and detecting biotechnology and hardware. Cuboctahedral bi-metallic structure is an often-quoted example of metal-natural polyhedra class. In this study, we have calculated the first and second Zagreb index, the augmented Zagreb index, and the inverse Randic, as well as general Randic index, the symmetric division, and harmonic index. We have also discussed these topological indices graphically and have found that the value of almost all indices goes higher and higher as the value of n goes higher.